2021
DOI: 10.2196/26964
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Preimplementation Perspectives of a Decision-Support Tool for the Prediction of Cardiac Arrhythmia Based on Machine Learning: Near-Live Feasibility and Qualitative Study

Abstract: Background Artificial intelligence (AI), such as machine learning (ML), shows great promise for improving clinical decision-making in cardiac diseases by outperforming statistical-based models. However, few AI-based tools have been implemented in cardiology clinics because of the sociotechnical challenges during transitioning from algorithm development to real-world implementation. Objective This study explored how an ML-based tool for predicting ventri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 77 publications
2
13
0
Order By: Relevance
“…In settings ranging from primary care clinics to hospital wards, explanations for ML predictions have been necessary to aid physician understanding and build trust. [22][23][24] Anesthesiology clinicians using a postoperative hypotension prediction system felt that different decision thresholds were needed for different patient groups, 8 similar to our finding that different thresholds should be used in different surgical populations. However, some user needs depend on the specific use case.…”
Section: Discussionsupporting
confidence: 76%
“…In settings ranging from primary care clinics to hospital wards, explanations for ML predictions have been necessary to aid physician understanding and build trust. [22][23][24] Anesthesiology clinicians using a postoperative hypotension prediction system felt that different decision thresholds were needed for different patient groups, 8 similar to our finding that different thresholds should be used in different surgical populations. However, some user needs depend on the specific use case.…”
Section: Discussionsupporting
confidence: 76%
“…We recommend focusing on the important local and sociotechnical context of each preimplementation site to meet the challenge of the "last mile" of implementation [11,21,22,30,31]. The positive attitudes and willingness to use AI-CDS tools we observed are positive indicators of the acceptance of this new technology [32,33], but they also underpin the idea that expectations should be aligned with the intended use of the AI-CDS tool to be adopted [17]. Moreover, it will be of value to repeat our questionnaire after the implementation of the AI-CDS tool for discharging ICU patients, as it has previously been observed that physicians showed As illustrated by the differences in familiarity and enthusiasm toward AI-CDS at the development and nondevelopment sites, sufficient attention should be paid to training and informing physicians on the use of the AI-CDS tool in their daily practice [10].…”
Section: Discussionmentioning
confidence: 92%
“…A recent scoping review of guidelines for the development of AI-CDS tools concluded that more focus on implementation strategy is needed for effective integration in the clinical setting [29]. Human-factors research, in the form of qualitative interviews and questionnaires, may enhance the uptake of AI-CDS tools, as this approach may improve the system's design, training process, and implementation strategies [12,17]. We recommend focusing on the important local and sociotechnical context of each preimplementation site to meet the challenge of the "last mile" of implementation [11,21,22,30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing AI systems for healthcare is a complex space with many, wide-ranging sociotechnical challenges [3,9,46,60,150], spanning: (i) concerns about patient autonomy and ability to explicitly consent or withdraw from healthcare data uses, and its privacy protection in AI development or use [123,134]; (ii) investigations into AI workflow integration [9,21,27] and how best to configure clinician-AI relationships to effectively empower care providers [50,54,125,141,147]; as well as (iii) challenges around acceptance, trust and adoption of AI insights into clinical practice [52,60,86,114,139]. This is mostly addressed in the field of eXplainable AI (XAI) through research into AI transparency via explanations and other mechanisms to help clinicians contest [53] or learn about AI outputs [24] to be able to develop an appropriate mental model of AI capabilities and their limitations.…”
Section: Human-centered Medical Aimentioning
confidence: 99%